IMPLEMENTASI PEMBUATAN BAHAN AJAR POCKET BOOK SEBAGAI UPAYA PENINGKATAN PEMAHAMAN KONSEP DAN KREATIVITAS MAHASISWA - Coryna Oktaviani; Mellyzar Mellyzar (Lantanida Journal, 2020)
This study aims to explain how creativity and conceptual understanding and their effects on chemistry education students through the assignment of a pocket book project. The method used was an experiment with a one shot case study design. This implementation was carried out for 20 even semester students of the 2018 Malikussaleh University Chemistry Education study program. The instruments used in this study were the student's creativity assessment sheet (conducted by the observer) and the conceptual understanding test questions (the form of an individual essay at the end of the lesson). The data obtained were then analyzed using a percentage formula and interpreted into a value interval. Based on the results obtained, the average student creativity was 81,33 categorized as good and understanding of the concept was 86. Creativity had an effect on students' conceptual understanding, because through the pocket books provided students could explore all their potential to complete the task. So that it can improve understanding of the concept of each student. For advanced researchers who want to do the same, to further expand the aspects assessed for the assessment of student creativity.